2010
DOI: 10.1080/10916460902744554
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Some Local Petroleum Residues by Spectroscopic Techniques

Abstract: Two vacuum residues were delivered from two different petroleum refineries, one from Suez Petroleum Company and the second from Alexandria Petroleum Company. Two heavy residues were subjected to solvent extraction using n-pentane, n-heptane, and ethyl acetate. The studied residues were fractionated into their components. Infrared spectroscopy was applied to study the distribution of functional groups contained in samples and their components. Some ratios calculated from the peak heights of selected infrared ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…UV–vis spectra of subfractions F 4 and F 5 present the Soret band, at approximately 408 nm, characteristic of vanadyl porphyrins. , It is well-known that petroporphyrins are highly associated with polar crude oil fractions such as asphaltenes, and complexation interactions take place between vanadium or nickel and molecules having N or O functionalities. In this sense, we could suggest high abundance of heteroatomic species in the subfractions F 4 and F 5 , supporting the presence of metalloporphyrins. , Finally, subfraction F 6 exhibits a narrow band between 230–262 nm, peaking at 254 nm, which corresponds to electronic transitions in conjugated aromatics or polyaromatics. , …”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…UV–vis spectra of subfractions F 4 and F 5 present the Soret band, at approximately 408 nm, characteristic of vanadyl porphyrins. , It is well-known that petroporphyrins are highly associated with polar crude oil fractions such as asphaltenes, and complexation interactions take place between vanadium or nickel and molecules having N or O functionalities. In this sense, we could suggest high abundance of heteroatomic species in the subfractions F 4 and F 5 , supporting the presence of metalloporphyrins. , Finally, subfraction F 6 exhibits a narrow band between 230–262 nm, peaking at 254 nm, which corresponds to electronic transitions in conjugated aromatics or polyaromatics. , …”
Section: Resultsmentioning
confidence: 54%
“…76,77 Finally, subfraction F 6 exhibits a narrow band between 230−262 nm, peaking at 254 nm, which corresponds to electronic transitions in conjugated aromatics or polyaromatics. 73,78 FT-ICR mass spectrometry analysis of samples F 1−6 reveals detailed molecular information. Figure 6 displays molecular weight distributions and compound class distributions of samples F 1−6 , and Figure 7 shows the contoured plots of 79 showed that the asphaltenic material is a valuable source of geochemical information, and occlusions can contain biomarkers such as pristane and phytane, squalene (C 30 H 50 ), steranes, and hopanes.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Intensities of the peaks in FTIR spectrum was further used to obtain the useful information regarding the viscous nature of the oil by calculating the degree of chain length and degree of branching of fatty acids of the oils. Absorbance of CH 3 symmetric deformation at 1375cm -1 and CH 2 + CH 3 symmetric deformation at 1460 cm -1 were used to calculate the degree of branching (A 1375 / A 1460 ) and degree of chain length (A 723 / A 1375 or A 723 / A 1460 ) is the ratio of absorbance of CH 2 rocking at 723cm -1 with the absorbance of CH 3 or CH 2 + CH 3 symmetric deformation [19][20] . The values of degree of chain length and degree of branching of oil samples after conventional heating and potato frying reported in the Table 4 revealed that these values were increased for both treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of the degree of branching was made by the ratios of A 1375 /A 1460 . The degree of chain length was measured by the ratio of absorbance band of CH 2 rocking vibration at 720 cm −1 and CH 2 +CH 3 or CH 3 symmetric deformation at 1375 cm −1 and 1460 cm −1, respectively, or A 720 /A 1460 or A 720 /A 1375 (El-Bassoussi et al, 2010).…”
Section: The Degree Of Chain Length and Degree Of Branchingmentioning
confidence: 99%